ICICI Bank Ltd. - Quintessence of Corporate Governance Failure and Board Ineffectiveness - Jain, Surbhi; Bagga, Teena; Aggarwal, Rashmi (Prabandhan: Indian Journal of Management, 2021)
The case study emerges from a controversy in which Chanda Kochhar, ICICI Bank’s former CEO, was alleged to have violated related party transactions at the behest of her husband, Deepak Kochhar. The bank had granted various loans to an associate of Deepak Kochhar, who in turn extended certain favors to Deepak Kochhar during Chanda Kochhar’s tenure as CEO. Do the loan approvals in banks have any ethical dilemmas attached to them? What is a conflict of interest? What is an enforceable quid-pro-quo? What are internal financial controls, and if these controls are robust, can they mitigate risk in an organization? This case study sought to answer these questions. Finally, the court found Chanda Kochhar liable for all allegations against her, marking a historic moment in Indian banking history.